Comprehensive transcriptome analysis of cochlear spiral ganglion neurons at multiple ages - Li, Chao (eLife, 2020)
Inner ear cochlear spiral ganglion neurons (SGNs) transmit sound information to the brainstem. Recent single cell RNA-Seq studies have revealed heterogeneities within SGNs. Nonetheless, much remains unknown about the transcriptome of SGNs, especially which genes are specifically expressed in SGNs. To address these questions, we needed a deeper and broader gene coverage than that in previous studies. We performed bulk RNA-Seq on mouse SGNs at five ages, and on two reference cell types (hair cells and glia). Their transcriptome comparison identified genes previously unknown to be specifically expressed in SGNs. To validate our dataset and provide useful genetic tools for this research field, we generated two knockin mouse strains: Scrt2-P2A-tdTomato and Celf4-3xHA-P2A-iCreER-T2A-EGFP. Our comprehensive analysis confirmed the SGN-selective expression of the candidate genes, testifying to the quality of our transcriptome data. These two mouse strains can be used to temporally label SGNs or to sort them.